2021
DOI: 10.3390/microorganisms9050921
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiotic Feed Developed with Lactobacillus delbrueckii subsp. delbrueckii TUA4408L and the Soymilk By-Product Okara Improves Health and Growth Performance in Pigs

Abstract: Lactobacillus delbrueckii subsp. delbrueckii TUA4408L is able to differentially modulate the innate immune response of porcine intestinal epithelial cells triggered by TLR4 activation. This strain also has a remarkable ability to grow on plant substrates. These two immunological and biotechnological characteristics prompted us to evaluate whether the soymilk by-product okara fermented with the TUA4408L strain can serve as an immunobiotic feed with the ability to beneficially modulate the intestinal immunity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 57 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…A potential alternative solution to these problems is the addition of naturally derived dietary additives, such as probiotics, that have enhancing effects on livestock health and productivity (Tables 1-3). Recent research with probiotic LAB in livestock suggested that the LAB might be used as an alternative strategy to antibiotic growth promoters [11,18,32,[59][60][61][62].…”
Section: Global Trends Of Antimicrobial Uses In Livestockmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential alternative solution to these problems is the addition of naturally derived dietary additives, such as probiotics, that have enhancing effects on livestock health and productivity (Tables 1-3). Recent research with probiotic LAB in livestock suggested that the LAB might be used as an alternative strategy to antibiotic growth promoters [11,18,32,[59][60][61][62].…”
Section: Global Trends Of Antimicrobial Uses In Livestockmentioning
confidence: 99%
“…The in vivo study by Islam et al (2021) revealed that immunobiotic feeding resulted in significant positive health benefits when using rakkyo pickled juice fermented with L. plantarum N14 in pigs, thus increasing feed intake, efficiency, and carcass quality [31]. In addition, another study by Suda et al (2021) suggested that the immunobiotic L. delbrueckii subsp. Delbrueckii TUA4408L okara feed significantly improved growth performance and meat quality in piglets [32].…”
Section: Application Of Probiotics In In Vivo Studies For Pig Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial intestinal microbiota improved, the amount of Lactobacillus and Lactococcus increased, and the immunity also increased. The piglets showed better meat quality and growth performance [ 68 ]. In addition, the use of L. delebureckii CCTCC M 207,040 as a diet supplement by Chen et al (2021) improved the gut structure resulting in increased gut integrity in lipolisaccharides (LPS)-challenged piglets.…”
Section: Prevention Of the Effects Of Piglet Weaning Based On The Use Of Labmentioning
confidence: 99%
“…Conversely, polysaccharidedegrading Prevotella increases after weaning [8]. As the efficiency by which the animal utilizes feed to reach the optimal body weight by the required finishing time, determines production performance [9], a healthy microbiota is deemed necessary to maintain the homeostasis and hence production performance of the piglet.…”
Section: Introductionmentioning
confidence: 99%